Basic characteristics of unjust enrichment in domestic and comparative law - Nikolova-Marković Aleksandra (Megatrend Revija)
In this scientific paper, an analysis of the basic characteristics of unjust enrichment in domestic and comparative law was made. During the research and preparation of scientific work, methods of analysis, inductive-deductive method and historical method were used. Unjust enrichment is a special source of obligation law. Its beginnings date back to Roman law, where condiction and version lawsuits were formed. The importance of unjust enrichment is reflected in the possibility of eliminating the violation of the principle of equivalence in the broadest sense of the word and returning material values to the subject to whom they belong by law. This paper will also include an analysis of the terminology of unjust enrichment, its definition, its dilemmas, the necessary conditions for its emergence, the effect, that is, the content of the obligation, both in domestic legislation and in comparative law.